2022
DOI: 10.24251/hicss.2022.138
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Model Compression and Ensemble Approach for Weed Detection

Abstract: Site-specific weed management is an important practice in precision agriculture. Current advances in artificial intelligence have resulted in the use of large deep convolutional neural networks for weed detection. In this paper, a transfer learning, model compression, and ensemble learning approach is introduced that is suitable for resource-limited hardware such as mobile and embedded devices. The resulting ensemble model achieves 91.2% classification accuracy which is comparable to the performance of state-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results presented by the SSD ResNet 50 model align with those shown by Ofori et al [39], where this model performed better than other DL models, including SSD Inception v2. Pearse et al [35] and Samiei et al [40] presented the ResNet model variations that performed slightly better than that proposed in this study (98% and 90%, respectively).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results presented by the SSD ResNet 50 model align with those shown by Ofori et al [39], where this model performed better than other DL models, including SSD Inception v2. Pearse et al [35] and Samiei et al [40] presented the ResNet model variations that performed slightly better than that proposed in this study (98% and 90%, respectively).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the phenotypic traits for phenological identification are restricted to leaves (e.g., number, size, and colour). Furthermore, considering that vegetable crops are often sown as mixed cropping, and the morphological traits of leaves are very similar between plants, especially in the early growth stages, it is difficult to identify the specific phenotypic traits in order to classify the phenophases of the corresponding plant (crops and weeds included) [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, training accurate models for image segmentation requires the production of hand annotated training datasets, which is time consuming and requires specialized expertise to properly annotate training image data ( Kamilaris and Prenafeta-Boldú, 2018 ). Further, the computing resources required for training and applying deep learning models are unique, more common to computer gaming systems or graphics design work, rather than traditional computational systems ( Gao et al, 2020 ; Ofori et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to related work, it becomes necessary to explore DL methods dealing with lower volumes such as transfer learning and model compression for more computationally efficient models. Ofori et al have several works showing that models with pre-trained weights outperform state-out-the-art CNNs [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding greener DL models in applications domains, we can find advances for greener DL-based solutions as well. For instance, for weed detection, Ofori et al combined the mobile-sized EfficientNet with transfer learning to achieve up to 95.44% classification accuracy on plant seedlings [20], and model compression achieving 62.22% smaller in size than DenseNet (the smallest-sized full-sized model) [21]. Moreover, for pig posture classification, Witte et al reported the YOLOv5 model achieving an accuracy of 99,4% for pig detection, and EfficientNet achieving a precision of 93% for pig posture classification [22].…”
Section: Green Aimentioning
confidence: 99%